The influence of self-efficacy and organizational climate on employee performance - Rizki Alfadillah Nasution Nasution; Ilham Syahputra Saragih (Enrichment : Journal of Management, 2023)
In this study, we investigated the relationship between organizational climate, employee performance, and employee self-efficacy. In the study's sample, there were 70 workers. Both multiple linear regression analysis and descriptive analysis were used in this study's data analysis. According to the findings of this study's significant partial test (t-test), the self-efficacy variable significantly and favourably affects employee performance. The value of t arithmetic (2.024) > t-table (1.669) and the organizational climate variable have a positive and significant effect on employee performance, as can be seen from the significance value of 0.000 < 0.05. t-count (2.004) > t-table (1.669) has a positive and significant effect on employee performance.